Characteristics and Challenge Faced By Socio-Technopreneur in Indonesia - Chairani Putri Pratiwi; Agung Hari Sasongko; Glory Aguzman; Rafki Chandra Wibawa; Rachmat Pambudy (School of Business, IPB University (SB-IPB), 2022)
Nowadays socio-technopreneurship as emerging trend among start-ups. The Covid-19 pandemic could be a factor in increasing the total number of socio-technopreneurs in Indonesia. The qualitative method was applied in this study. The descriptive analysis research method was used to collect data, conduct interviews with founder, CEO and business manager, and gather evidence. The study's objectives are to define the character of a socio-technopreneur and to analyze the obstacles and challenges that socio-technopreneurs face in Indonesia. The results show the character of a socio-technopreneur as (1) collaborative, (2) concerned with a social mission, (3) have creative and innovative ideas, (4) confident, (5) dare to take risks and challenges, (6) have a leadership spirit, (7) optimism, and (8) adopt with digital/technology. Some tenants, who are MSMEs or farmers, have difficulties or are unfamiliar with the system or procedure, even after it has been demonstrated to them. Second, the use of technology or digital marketing by socio-technopreneurs creates opportunities for a larger market. In the middle of today's challenges, there are several opportunities for people to improve their wealth by becoming entrepreneurs who shift into socio-technopreneurs. Socio-technopreneurship is a critical aspect in the growth of the Indonesian economy, particularly the local economy. The growth of socio-technopreneurship based on social mission and technology adoption can accelerate the development of technological entrepreneurship, reduce social issues, create new jobs, contribute to technology transfer and innovation, and strengthen national economic growth. Keywords: entrepreneurship, local economy, social, start-up, technology